A systematic review of attributes used in choice experiments for agri-environmental contracts - Nidhi Raina; Matteo Zavalloni; Stefano Targetti; Riccardo D'Alberto; Meri Raggi; Davide Viaggi (Bio-based and Applied Economics (BAE), 2021)
Contract attributes are strong motivators for eliciting farmers' preferences for a particular agri-environmental scheme. Our study aims to conduct a systematic literature review to highlight the attributes used in choice experiment studies of agri-environmental schemes using the PRISMA framework. We obtained 34 studies for an in-depth review, through which we extracted 32 attributes that were classified into five typologies: 'monetary' (7 attributes), 'general' (4 attributes), 'flexibility' (6 attributes), 'prescription' (12 attributes), and 'purpose' (3 attributes). Though monetary attributes should theoretically define farmers' choices; general design and flexibility attributes are more critical for farmers' participation and willingness to accept. The study also discusses the lesser-used attributes that could be potentially explored in future studies. Thus, our review can be used as a reference by future AES studies to select their bundle of choice attributes and test with a broader range of attributes in their choice experiments.
Keywords: Q15; Q20; Q57; 330; choice experiment; agri-environmental schemes; willingness to accept; contract attributes; systematic literature review